Nonenzymatic antioxidants of blood in multiple sclerosis - Karg Eszter (JOURNAL OF NEUROLOGY, 1999)
Free radical action has been suggested as a causal factor in multiple sclerosis. We investigated the plasma level of lipid peroxides expressed in terms of malone dialdehyde and changes in blood nonenzymatic antioxidants (glutathione, alpha-tocopherol, retinol, plasma sulfhydryl groups, and uric acid) in multiple sclerosis patients with exacerbation or in remission, including a group treated with beta-interferon. The malone dialdehyde level was increased by 38% (n.s.) during exacerbations. The blood concentration of oxidized glutathione was likewise elevated (P<0.05), while the ratio of plasma alpha-tocopherol to cholesterol plus triglyceride was decreased (P<0.001). These changes suggest increased free radical production and consumption of the scavenger molecules during the active phase of the disease. Blood reduced glutathione level was increased (P<0.01) during exacerbation and remission as well. The rise in this thiol is likely to be a compensatory mechanism defending the cells from further oxidant injuries. Beta-interferon increased plasma alpha-tocopherol levels (P<0.001) but not the lipid corrected alpha-tocopherol value. Other parameters were not influenced by the drug.